Numerical Simulation of Solar Granulation Dynamics Using Optical Correction Techniques - Ali, Huda Shaker (Iraqi Journal of Science, 2025)
High-resolution imaging of celestial bodies, especially the sun, is essential for understanding dynamic phenomena and surface details. However, the Earth's atmospheric turbulence distorts the incoming light wavefront, which poses a challenge for accurate solar imaging. Solar granulation, the formation of granules and intergranular lanes on the sun's surface, is important for studying solar activity. This paper investigates the impact of atmospheric turbulence-induced wavefront distortions on solar granule imaging and evaluates, both visually and statistically, the effectiveness of Zonal Adaptive Optics (AO) systems in correcting these distortions. Utilizing cellular automata for granulation modelling and Zonal AO correction methods, the study aims to understand system behavior under varying atmospheric turbulence conditions and provide recommendations for Zonal AO system enhancement for solar observations. Performance metrics, including Strehl Ratio, Correction Stability, Root Mean Squared Error (RMSE), and Correction Rate, were used to assess system performance under varying turbulence levels. However, challenges arise with increasing turbulence strength, impacting correction precision, stability, and speed. The results showed the weakness of the Zonal AO in treating high distortions in wavefront, as is evident by the decreases in Strehl Ratio values from 0.98 to 0.085 for disturbance strength values from 0.2 to 1, respectively.